Roads to Commensurability - Pearce, D. author. aut Link
XI, 260 p.
Keywords: How many miles to Babylon? Three-score and ten. Can I get there by candle-light? Yes, and back again. If your heels are nimble dnd light, You may get there by candle-light. Any philosopher who takes more than a fleeting interest in the sciences and their development must at some stage confront the issue of incommensurability in one or other of its many manifes tations. For the philosopher of science concerned with problems of conceptual change and the growth of knowledge, matters of incommensurability are of paramount concern. After many years of skating over, skimming through and skirting round this issue in my studies of intertheory relations in science, I decided to take the plunge and make the problem of incommensurability the central and unifying theme of a book. The present volume is the result of that decision. My interest in problems of comparability and commensurability in science was awakened in the formative years of my philosophi cal studies by my teacher, Jerzy Giedymin. From him I have learnt not only to enjoy philosophical problems but also to beware of simpleminded solutions to them. The vibrant seminars of Paul Feyerabend held at Sussex University in 1974 left me in no doubt that incommensurability was, and would remain, a major topic of debate and dispute in the philosophical study of human knowledge.